Development of hormone system teaching material for distance learning to improve students digital literacy - Ian Fadilah; Rusdi Rusdi; Rizhal Hendi Ristanto (Jurnal Pijar Mipa, 2023)
This research aims to develop hormone system teaching material for distance learning DL through Moodle to improve students' digital literacy. This research uses the Research and Development (R&D) method with the ADDIE model, which has the stages of analysis, design, development, implementation, and evaluation. The developed teaching material was tested for feasibility on the material, media, and language aspects by six expert validators. Two biology teachers and students from senior high school SMAN 3 Bekasi also tested the developed teaching material. The results showed that the hormone system teaching material for DL through Moodle had an average value of 3.40 (very valid) on the material aspect, 3.30 (very valid) on the media aspect, and 3.03 (valid) on the language aspect. The Biology teacher’s trial obtained an average value of 3.45 (very valid) and an average of 3.32 (very valid) for the students’ trial. The hormone system teaching materials for DL through Moodle has a final average value of 3.30 from a maximum value of 4.00. It shows that the hormone system teaching material for DL through Moodle is very valid to be used as a learning medium for hormone systems in schools and is expected to improve students' digital literacy.